2022
DOI: 10.1159/000527745
|View full text |Cite
|
Sign up to set email alerts
|

Can Informal Caregiving be Perceived as Rejuvenating? Changes in Perceptions of Ageing at Onset and End of Informal Caregiving during Different Stages of Life

Abstract: <b><i>Introduction:</i></b> Perceptions of ageing are a central predictor of health, wellbeing, and longevity. This study analyses the association between the onset and end of informal caregiving and perceptions of ageing in different stages of life. <b><i>Methods:</i></b> Data from the German Aging Survey (2014, 2017) were used; a longitudinal dataset that is representative of community-dwelling individuals aged ≥40 years in Germany. Adjusted asymmetric fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
0
5
1
Order By: Relevance
“…In previous research male caregivers often reported difficulties with caregiving and having to learn new skills, such as cooking, cleaning and personal care (Russell 2007 ). They were also less likely to be involved in personal care (Pinquart and Sörensen 2006 ; Zygouri et al 2021 ). More diversity of tasks may thus not provide more variety and highlight one’s own abilities, as found among female caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous research male caregivers often reported difficulties with caregiving and having to learn new skills, such as cooking, cleaning and personal care (Russell 2007 ). They were also less likely to be involved in personal care (Pinquart and Sörensen 2006 ; Zygouri et al 2021 ). More diversity of tasks may thus not provide more variety and highlight one’s own abilities, as found among female caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, male and female caregivers would benefit from decreasing the number of care hours per week, as mentioned above. Since enabling diversity in care tasks seems to be only helpful for female caregivers’ views of ageing, reduction of care hours should not be achieved by reducing the range of care tasks among female caregivers and leaving them to provide, for example, only personal care, which is often the care task female caregivers are mainly involved in (Pinquart and Sörensen 2006 ; Stanfors et al 2019 ; Zygouri et al 2021 ). Instead, designing care support that reduces intensity not diversity, especially among older and female caregivers, is recommended, to foster more positive personal views of ageing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, all these aspects are also known to affect health [28]. Based on the literature, the beginning of informal care is significantly associated with a better attitude toward old age, while the end of informal care is significantly associated with an increase in subjective age and an earlier onset of old age [29]. Measuring the self-perception of aging among informal caregivers is vital for understanding their attitudes and expectations regarding their caregiving role.…”
Section: Introductionmentioning
confidence: 99%